Structural Basis for the Prenylation Reaction of Carbazole‐Containing Natural Products Catalyzed by Squalene Synthase‐Like Enzymes. (16th March 2022) - Nagata, Ryuhei; Suemune, Hironori; Kobayashi, Masaya; Shinada, Tetsuro; Shin‐ya, Kazuo; Nishiyama, Makoto; Hino, Tomoya; Sato, Yusuke; Kuzuyama, Tomohisa; Nagano, Shingo
Abstract: Some enzymes annotated as squalene synthase catalyze the prenylation of carbazole‐3, 4‐quinone‐containing substrates in bacterial secondary metabolism. Their reaction mechanisms remain unclear because of their low sequence similarity to well‐characterized aromatic substrate prenyltransferases (PTs). We determined the crystal structures of the carbazole PTs, and these revealed that the overall structure is well superposed on those of squalene synthases. In contrast, the stacking interaction between the prenyl donor and acceptor substrates resembles those observed in aromatic substrate PTs. Structural and mutational analyses suggest that the Ile and Asp residues are essential for the hydrophobic and hydrophilic interactions with the carbazole‐3, 4‐quinone moiety of the prenyl acceptor, respectively, and a deprotonation mechanism of an intermediary σ‐complex involving a catalytic triad is proposed. Our results provide a structural basis for a new subclass of aromatic substrate PTs. Abstract : Carbazole prenyltransferase was found to combine the overall structure of squalene synthase and the elegant stacking interaction between prenyl diphosphate and aromatic compounds observed in the aromatic substrate prenyltransferase. Structural and mutational analyses revealed the binding and deprotonation mechanisms of the carbazole‐3, 4‐quinone moiety of the prenyl acceptor.